Amalan pengurusan akuakultur baik dan kecekapan teknikal sistem ternakan kolam di negeri Kedah dan Pulau Pinang, Malaysia - Rozana, Samah (2017)
Good aquaculture management practices and efficient production activity that take into account socio-economic and environmental aspects are crucial to achieve sustainable aquaculture development and to ensure the continuation of national food security. The objectives of this study are to identify the level of aquaculture production, determine the level of good aquaculture management practices, analyze the technical efficiency of aquaculture production, and estimate the impact of good aquaculture management practices on the level of technical efficiency of aquaculture production. A survey on 121 brackishwater and freshwater pond aquaculture farmers in Kedah and Pulau Pinang, Malaysia was conducted to obtain data and information. Data Envelopment Analysis (DEA) was employed to estimate the technical efficiency score of aquaculture production. Tobit regression model was used to identify the impact of good aquaculture management practices on technical efficiency of aquaculture production. Results reveal that average aquaculture production of freshwater pond was higher than brackishwater pond culture system. However, the level of good aquaculture management practices and the level of technical efficiency among freshwater pond farmers were lower than brackishwater pond farmers. The aspects of seed, food, health and postharvest managements are significant factors influencing the level of technical efficiency of aquaculture production in the study area. This study clearly exhibits the importance of good aquaculture management practices in increasing the level of technical efficiency of aquaculture production. Thus, measures such as enforcement and encouragement towards good aquaculture management practices need to be intensified to increase the level of good aquaculture management practices among farmers. This is very important to ensure the sustainable development of aquaculture in Malaysia.